Eosinophils and Mast Cells in Aspirin-Exacerbated Respiratory Disease - Steinke, John W. (Immunol Allergy Clin North Am, 2016)
Aspirin-exacerbated respiratory disease (AERD) is explained in part by over-expression of pro-inflammatory mediators including 5-lipoxygenase and leukotriene C(4) synthase (LTC(4)S) that results in constitutive over-production of cysteinyl leukotrienes (CysLTs). Mast cells and eosinophils are two cell types that have important roles in mediating many of the effects observed in this disease. Increased levels of both interleukin (IL-4) and interferon (IFN)-γ are present in the tissue of AERD subjects. Previous studies demonstrated that IL-4 is primarily responsible for the upregulation of LTC(4)S by mast cells. Our studies demonstrate that IFN-γ, but not IL-4 drives this process in eosinophils. We also extend to both IL-4 and IFN-γ the ability to upregulate CysLT receptors. Prostaglandin E(2) (PGE(2)) acts to prevent CysLT secretion by inhibiting mast cell and eosinophil activation. PGE(2) concentrations are reduced in AERD and studies confirm that this reflects diminished expression of cyclooxygenase (COX)-2, a process again that is driven by IL-4. Thus, IL-4 and IFN-γ acting on eosinophils and mast cells together play an important pathogenic role in generating the phenotype of AERD. This review will examine the overall role that eosinophils and mast cells contribute to the pathophysiology of AERD.